Continuous fibre-reinforced thermoplastic acrylic-matrix composites prepared by liquid resin infusion – A review. (15th June 2021) - Obande, Winifred; Ó Brádaigh, Conchúr M.; Ray, Dipa
Abstract: Increasing demand for lightweight materials is a major driving force for the steady growth of the continuous fibre-reinforced polymer composite industry. In recent years, strict global targets demanding greater environmental responsibility have led to a shift in research focus to address the end-of-life challenges posed by the use of thermoset matrices. Thermosets offer lower-cost processibility than thermoplastics, which historically required cost- and energy-intensive production methodologies. Consequently, despite their well-demonstrated recyclability, thermoformability and weldability, thermoplastics are yet to attain the same technological maturity as thermosets. In situ polymerisable thermoplastic resins have been identified as attractive emerging solutions for improving the processibility of thermoplastics. Thus, are essential materials in meeting the demand for fibre-reinforced thermoplastic composites. This review presents a comprehensive summary of recent works on room-temperature-processible liquid thermoplastic acrylic resins and their composites. Moreover, open problems and research opportunities are identified and discussed. Graphical abstract: Image 1 Highlights: The progress on novel liquid thermoplastic acrylic composite resins is reviewed. Factors affecting the in-situ polymerisation of acrylic resins are overviewed. Performance tailoring methodologies for acrylic-matrix composites are discussed. Recent advances in hybrid and multi-material acrylic-based materials are summarised. Challenges and exploration opportunities for liquid acrylic resins are proposed.